Using Dendritic Cell-Based Immunotherapy to Treat HIV: How Can This Strategy be Improved? - da Silva, Laís Teodoro; Santillo, Bruna Tereso; de Almeida, Alexandre; Duarte, Alberto Jose da Silva; Oshiro, Telma Miyuki (Frontiers in Immunology, 2018)
Harnessing dendritic cells (DC) to treat HIV infection is considered a key strategy to improve anti-HIV treatment and promote the discovery of functional or sterilizing cures. Although this strategy represents a promising approach, the results of currently published trials suggest that opportunities to optimize its performance still exist. In addition to the genetic and clinical characteristics of patients, the efficacy of DC-based immunotherapy depends on the quality of the vaccine product, which is composed of precursor-derived DC and an antigen for pulsing. Here, we focus on some factors that can interfere with vaccine production and should thus be considered to improve DC-based immunotherapy for HIV infection.